Sumber Daya Manusia dan Manajemen Puskesmas dalam Mencapai Indikator Rasio Peserta Prolanis Terkendali (RPPT) di Kabupaten Situbondo - Adinda Dwi Lestari; Eri Witcahyo; Christyana Sandra (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
The achievement of the controlled prolanis participant ratio indicator as one of the three indicators in the implementation of the Performance-Based Capitation payment system at public health center is considered not optimal because several puskesmas in Situbondo Regency have not been able to meet the target indicator. This research was a qualitative study, where data collection was carried out through in-depth interviews by examining more deeply matters related to human resources and health center management in achieving a controlled prolanis participant ratio indicator. The results showed that problems related to achieving the target ratio of controlled prolanis participants were caused by informants' knowledge that still referred to the number of visiting prolanis participants, not to the number of controlled prolanis participants. This has an impact on the planning of puskesmas related to strategy formulation in achieving the targets and objectives of the implementation of prolanis activities which are not optimal because they are not in accordance with the applicable capitation regulations, lack of coordination and low participation of participants.Keywords: controlled prolanis participant ratio indicator; performance-based capitation; public health center ABSTRAK Pencapaian indikator rasio peserta prolanis terkendali sebagai salah satu dari tiga indikator dalam pelaksanaan sistem pembayaran Kapitasi Berbasis Kinerja pada puskesmas dinilai belum maksimal karena beberapa puskesmas di Kabupaten Situbondo belum mampu memenuhi target indikator tersebut. Penelitian ini merupakan studi kualitatif, dimana pengambilan data dilakukan melalui wawancara mendalam dengan mengkaji lebih dalam hal-hal terkait sumber daya manusia dan manajemen puskesmas dalam mencapai indikator rasio peserta prolanis terkendali. Hasil penelitian menunjukkan bahwa permasalahan terkait pemenuhan pencapaian target rasio peserta prolanis terkendali disebabkan karena pengetahuan informan yang masih mengacu pada jumlah peserta prolanis berkunjung, bukan pada jumlah peserta prolanis terkendali. Hal tersebut berdampak terhadap perencanaan puskesmas terkait penyusunan strategi dalam mencapai target dan tujuan dari pelaksanaan kegiatan prolanis tidak maksimal karena tidak sesuai dengan peraturan kapitasi yang berlaku, kurangnya koordinasi serta rendahnya partisipasi peserta.Kata kunci: indikator rasio peserta prolanis terkendali; kapitasi berbasi kinerja; puskesmas